Strategi Mempertahankan Popularitas Melalui Kegiatan Promosi Media Digital (Studi Kasus Pada Produksi Musik Hendra Kumbara) - Fatima, Sephia Putri; Wrahatnala, Bondet; Manggala, Bondan Aji (Acintya, 2023)
Every year the music industry displays new musicians, and each has their characteristics in their work. Of course, there will be many contemporary artists with different characters. One of the music industry’s strategies is to increase marketing in music production. This is not only a matter of promotion, but the music industry is also thinking about stealing attention, building loyalty, encouraging action, and how to educate and entertain through the content that is presented. Hendra Kumbara is a Javanese musician who has popularity among young people in the digitalization era; Dalan Liyane’s song is one of the works that support his popularity in digital media. In addition, he also developed the music industry for creative space in the city of Semarang. This study aims to determine Hendra Kumbara’s music production strategy for maintaining its popularity through digital media promotion activities. The research used is a qualitative method with a case study approach, with data collection techniques through observation, interviews, and literature studies selected according to the topic of discussion regarding musical creativity in maintaining popularity through digital media. The survey results prove that: (1) Hendra Kumbara’s music production supports popularity through digital media promotion activities by knowing the concept of music production and marketing strategies through digital media platforms. (2) strategies carried out by knowing musical abilities and marketing musical works through digital media platforms Youtube, Instagram, TikTok, Spotify, Joox, Tunes, Apple Music, and Deezer.Keywords: strategy, popularity, musicians, digital media.